If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (1ab * 3xy) + -1n = 0 Reorder the terms for easier multiplication: (1 * 3ab * xy) + -1n = 0 Multiply 1 * 3 (3ab * xy) + -1n = 0 Multiply ab * xy (3abxy) + -1n = 0 Solving (3abxy) + -1n = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add 'n' to each side of the equation. (3abxy) + -1n + n = 0 + n Combine like terms: -1n + n = 0 (3abxy) + 0 = 0 + n (3abxy) = 0 + n Remove the zero: (3abxy) = n Divide each side by '(3bxy)'. a = 0.3333333333b-1nx-1y-1 Simplifying a = 0.3333333333b-1nx-1y-1
| 4+5=3x | | (3x+4)=(x-5) | | 10/15=x/80 | | f(7)=2x+1 | | 7(y+2)=21 | | f(7)=2+1 | | 2/3v=2-43 | | -24-3r=9 | | x*2+9x+7=0 | | 2(d-6)=3d-1 | | 3/2p-2=-1 | | 2a=220-6y | | 1.5x-2=3 | | 50x^2-100xy+50y^2=0 | | X-(-12)=23 | | b+166=-3b-6 | | 2b+6.3=13.2-28 | | -9x-5=x+385 | | x^2+10x+25+y^2-18y+81=64 | | a-324=-6a-9 | | a^3=512 | | -9z+4=z+234 | | 10x-11-rx=43 | | u+133=-9u+3 | | y/6-1/3=2 | | b+59=-b-5 | | 1/2m-3=2 | | b+59=b-5 | | z-58=-z-8 | | 2x+8=4x+22 | | -a+8=a+98 | | B-56=234 |